Chapter Contacts between indigenous languages in South America - Muysken, Pieter (De Gruyter, 2012)
This chapter I will try to describe a few aspects of language contact in the history of the languages of the American Indian communities of South America. The topic ofcontacts between the indigenous languages in South America is vast and almost in-tractable. This is the case particularly because we still know little about the history of the languages of the continent, in the absence of essential sources of informatin, which include: - historical sources dating back more than a few centuries - reliable and complete descriptions for the majority of languages or major representatives of language families - reliable family trees for a number of linguistic families - reliable reconstructions of the features of potential ancestor languages